A Systematic Approach to Provide Feedback to Presenters at Virtual and Face-to-Face Professional Meetings - S. Beth Bierer; Anna Cianciolo; Heeyoung Han; Janice Hanson (Association of American Medical Colleges, 2022)
Introduction To promote their personal and professional growth, medical educators need practical, actionable feedback on their scholarship, as well as guidance for documenting their scholarship in educator portfolios. We offer a framework and resources to provide formative and summative feedback to faculty, administrators, and/or learners delivering an oral presentation at a face-to-face or virtual health professions education meeting. Methods In 2014, the leadership of the Central Group on Educational Affairs (CGEA) meeting planning committee developed and piloted a process to provide individuals with formative and summative feedback on their oral CGEA research presentations at face-to-face meetings and create a transparent process for determining the Best Presentation Award. The feedback process was implemented for 7 years until revised in 2021 for the CGEA's first virtual meeting. Past and present meeting organizers conducted four focus groups in 2021 with presenters and peer reviewers via Zoom. Transcripts were analyzed for major themes using conventional content analysis. Results To date, 102 presentation assessments have been conducted, including formative and summative assessments. Sixty-two volunteer assessors have participated, 19 (31%) of whom served for more than 2 years. Focus groups identified best practices and suggestions to improve the feedback process. Discussion This resource offers a feasible, systematic process to provide individuals with formative feedback on presentations at professional conferences, promote a community of practice for personal and professional development, and create a transparent process for determining a Best Presentation Award. Participants valued providing and receiving feedback and recommended implementation at other professional meetings.